Oxacillinase-484–Producing Enterobacterales, France, 2018–2023 - Cécile Emeraud; Sandrine Bernabeu; Delphine Girlich; Inès Rezzoug; Agnès B. Jousset; Aurélien Birer; Thierry Naas; Rémy A. Bonnin; Laurent Dortet (Emerging Infectious Diseases, 2024)
We examined the emergence and characteristics of oxacillinase-484–producing Enterobacterales in France during 2012–2023. Genomic analysis identified 2 predominant sequence types in Escherichia coli: ST410 and ST1722. Plasmid analysis revealed that blaOXA-484 genes were carried mostly on an IncX3-type plasmid associated with genetic elements including insertion sequences IS3000 and ISKpn19.